PENGOLAHAN LUMPUR (SLUDGE) LIMBAH PENCELUPAN DENGAN CARA KOMPOSTING - Suyasa, I.W. Budiarsa (Bumi Lestari, 2010)
Sludge of waste treatment represent main problem of processing chemically because needing special handling. Processing of this mud cost money which quite a lot, at least 50% from expense of processing of waste water needed to to overcome yielded mud, as a result most in Indonesia this direct mud thrown to river or piled up. Treatment of sludge was composting with inoculate microorganism from several of sediment and soil. Phase of seeding was conducted by addition of NPK and other micro-nutrient in 3 L of basin. Growth of microorganism was measured of each every 2 day during one week with measuring value of biomass till reach price 2000 mg / L. Active mud as product inoculated to composting process of organic material with sludge. All active mud result of seed into each place of that is Place of A : active mud of river sediment of Badung, Place of B : active mud of moat sediment, place of C : active mud of fertile land, Place of D : without addition of active mud as control. Change of fastest physical happened at sample with addition of active mud from fertile land. Degradation of rate of C organic and highest total N happened at sample with addition from active mud of moat, while highest available K happened at sample with addition from active mud of fertile land. Rate of N highest total obtained by sample with addition from active mud of River of Badung and from fertile land. Product of composting process were fulfill SNI (19-7030-2004) for the parameter of physical that is temperature, color and odour